Determination of proximate composition, amino acids, minerals and phytochemical profile of Cassava (Manihot esculenta) peel from sweet cassava variety grown in Yobe State of North Eastern Nigeria - Amaza , I. B. (Nigerian Journal of Animal Production, 2021)
The proximate composition, amino acid, mineral, and Phytochemical content of Cassava peel was determined. The peels were found to contain 8.70 % moisture, 4.89 % crude protein, 8.75 % crude fiber, 2.15 % crude fat, 8.93 % ash. Nitrogen free extract and metabolizable energy values were 66.56 % and 2717.96kcal, respectively. The results of amino acid content revealed that the histidine and tyrosine are the most limiting amino acid with values of 0.005% each. Essential amino acids such as lysine, leucine, methionine and Isoleucine with values of 0.032, 0.067, 0.076 and 0.070% were low. Mineral profile revealed that magnesium (913.74mg/kg) and iron (111.50mg/kg) as the most abundant mineral. Concentrations of phytochemicals were 26.06, 699.8, 0.063, 24.81,8.37,1457mg/100g and 2.84 for saponin, tannin, hydrogen cyanide, phytate, trypsin inhibitors, alkaloid and oxalate respectively. Based on results of this study, cassava peel can be potential source of energy; however, protein and amino acids contents are very low. It is therefore, recommended that feeding of animal with cassava peel based diets be supplemented with good quality amino acids. La composition immédiate, l'acide aminé, la teneur minérale et phytochimique de la peau de manioc ont été déterminées. Les pelures contenaient 8,70 % d'humidité, 4,89 % de protéines brutes, 8,75 % de fibres brutes, 2,15 % de matières grasses brutes, 8,93 % de cendres. L'extrait sans azote et les valeurs énergétiques métabolisables étaient respectivement de 66,56 % et 2 717,96 kcal. Les résultats de la teneur en acides aminés ont révélé que l'histidine et la tyrosine sont l'acide aminé le plus limitant avec des valeurs de 0,005% chacune. Les acides aminés essentiels tels que la lysine, la leucine, la méthionine et l'isoleucine avec des valeurs de 0,032, 0,067, 0,076 et 0,070% étaient faibles. Le profil minéral a indiqué que le magnésium (913.74mg/kg) et le fer (111.50mg/kg) sont des minéraux les plus abondants. Les concentrations de produits phytochimiques étaient de 26,06, 699,8, 0,063, 24,81,8,37,1457mg/100g et 2,84 pour la saponine, le tanin, le cyanure d'hydrogène, le phytate, les inhibiteurs de la trypsine, l'alcaloïde et l'oxalate respectivement. D'après les résultats de cette étude, la peau de manioc peut être une source potentielle d'énergie ; cependant, la teneur en protéines et en acides aminés est très faible. Il est donc recommandé que l'alimentation des animaux avec des régimes à base de pelures de manioc soit complétée par des acides aminés de bonne qualité.